2019
DOI: 10.1177/2473974x19826943
|View full text |Cite
|
Sign up to set email alerts
|

Speech and Language Outcomes in Patients with Ankyloglossia Undergoing Frenulectomy: A Retrospective Pilot Study

Abstract: Ankyloglossia is a controversial topic with no standardized treatment guidelines. A retrospective chart review was conducted to identify children who underwent lingual frenulectomy for speech and language impairment. Impairment severity was recorded pre- and postoperatively as mild, mild to moderate, moderate, moderate to severe, or severe. Variables were tested with chi-square analysis for their statistical relationship to improvements in speech and language. Children with preoperative moderate and moderate-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…The study selection process is shown in Figure 1. In total, 16 studies 4,5,13,15‐27 with a total sample size of 2244 participants were included in this systematic review for further analysis. Figure 1 indicates a flowchart of the studies included in the selection process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study selection process is shown in Figure 1. In total, 16 studies 4,5,13,15‐27 with a total sample size of 2244 participants were included in this systematic review for further analysis. Figure 1 indicates a flowchart of the studies included in the selection process.…”
Section: Resultsmentioning
confidence: 99%
“…In a review article in 2020, Khan et al explained that the controversial conclusions on articulation that were drawn across the different studies were due to heterogeneity in the outcome measurements and the lack of appropriate statistical comparisons 7 . Additionally, Daggumati et al 13 pointed out the lack of accepted guidelines on the management of ankyloglossia as an additional possible factor contributing to this controversy.…”
Section: Introductionmentioning
confidence: 99%
“…studies have conflicting results and the outcome measures are different [7][8][9][10]. Therefore, there is no universal consensus on how to approach ankyloglossia regarding future speech problems.…”
Section: Original Articlementioning
confidence: 99%
“…4 Last, Daggumati treated 48 children and found that those with moderate speech impairment benefited more than those with mild impairment. 5…”
Section: Introductionmentioning
confidence: 99%
“…4 Last, Daggumati treated 48 children and found that those with moderate speech impairment benefited more than those with mild impairment. 5 Most tongue-tie research focuses on breastfeeding, with several randomized controlled trials and other studies demonstrating benefit to the nursing dyad. [6][7][8][9][10][11] Solid feeding issues were not reported to occur with tongueties until a 2018 case series linking 5 children with posterior tongue restrictions to feeding difficulties.…”
Section: Introductionmentioning
confidence: 99%